Nonlinear-Optical Processing of OAM Light States in a Few-Mode Fiber - Cheng Guo; Afshin Shamsshooli; Francesca Parmigiani; Xiaoying Li; Michael Vasilyev (Photonics)
Utilizing the phase-matching conditions of inter-modal four-wave mixing in an elliptical-core few-mode fiber supporting three non-degenerate modes, we experimentally demonstrate schemes for generating orbital-angular-momentum (OAM)-entangled photon pairs with high mode purity and for achieving highly mode-selective frequency conversion of beams in OAM-compatible (LP11a, LP11b) mode basis. These techniques expand the toolbox for using OAM modes in both classical and quantum communications and information processing.